Sisterhood Depicted in 2037 (Two Zero Three Seven) (2022) - Krisnawati, Rindang (LITERA KULTURA : Journal of Literary and Cultural Studies, 2024)
Feminism and gender are prominent topic in literature. One of the movies that focuses on feminism and gender is 2037. This movie tells a story about Yoon Young journey in the prison, which is the main characters of the movie. Yoon Young is a 19-year-old girl who got raped and sentenced because she is accidentally killed her rapist. This study analyses the depiction of sisterhood in the film 2037 by utilizing the sisterhood theory proposed by bell hooks. The findings reveal that the depiction of sisterhood in 2037 is depicted through sharing resources and strength, sharing knowledge, compassion, stand up for each other, last is collaboration and unity. In addition, sisterhood also influence the main characters life in prison. How she can adapt quickly in such situation, was able to speak up for herself, and did not give up on her dreams.